Hypertension: Salt restriction, sodium homeostasis, and other ions - Gupta, Neeru; Jani, KishanKumar; Gupta, Nivedita (Indian journal of medical sciences, 2011)
Salt is composed of Sodium Chloride (NaCl) which in body water becomes essential electrolytes, viz., Sodium (Na + ) and Chloride (Cl - ) ions, including in the blood and other extracellular fluids (ECF). Na + ions are necessary cations in muscle contractions and their depletion will effect all the muscles in body including smooth muscle contraction of blood vessels, a fact which is utilized in lowering the blood pressure. Na+ ions also hold water with them in the ECF. Na + homeostasis in body is maintained by thirst (water intake), kidneys (urinary excretion) and skin (sweating). In Na + withdrawal, body tries to maintain homeostasis as far as possible. However, in certain conditions (e.g., during exercise, intake of drugs and in disorders causing Syndrome of Inappropriate Anti Diuretic Hormone Secretion (SIADH), diuretics, diarrhea) coupled with moderate or severe dietary salt restriction (anorexia nervosa), hyponatremia can get precipitated. Hyponatremia is one end point in the spectrum of disorders caused by severe Na + depletion whereas in moderate depletion it can cause hypohydration (or less total body water) and lower urinary volume (U v ). Moreover, salt sensitivity varies in various populations leading to different responses in relation to dietary Na + intake. Diabetes and Hypertension often co-exist but Na + withdrawal in salt sensitive subjects worsens diabetes though hypertension gets better and reverse occurs in salt loading. Therefore, Na + or salt restriction may be non-physiological. In hypertensive subjects other alternatives to Na + withdrawal could be Potassium (K + ) and Calcium (Ca 2+ ) supplementation. Further studies are required to monitor safety/side effects of salt restriction. [PUBLICATION ABSTRACT]